2012
DOI: 10.1038/cddis.2012.136
|View full text |Cite
|
Sign up to set email alerts
|

Remnant living cells that escape cell loss in late-stage tumors exhibit cancer stem cell-like characteristics

Abstract: A balance between cell proliferation and cell loss is essential for tumor progression. Although up to 90% of cells are lost in late-stage carcinomas, the progression and characteristics of remnant living cells in tumor mass are unclear. Here we used molecular imaging to track the progression of living cells in a syngeneic tumor model, and ex vivo investigated the properties of this population at late-stage tumor. The piggyBac transposon system was used to stably introduce the dual reporter genes, including mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…To induce insertional mutagenesis and observe mutant cells, we used the PB-3R-puro construct 18 , 23 , 24 , which encodes a PB transposable element carrying a red fluorescence protein (RFP) for visualization of electroporated cells by fluorescent microscopy. When the brains were electroporated with PB alone or a control pCAG-GFP construct expressing green fluorescence protein (GFP) at E14.5, the fluorescently labeled cells were primarily found within layers 2/3 and 4 of cortex on postnatal day 10 (P10) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To induce insertional mutagenesis and observe mutant cells, we used the PB-3R-puro construct 18 , 23 , 24 , which encodes a PB transposable element carrying a red fluorescence protein (RFP) for visualization of electroporated cells by fluorescent microscopy. When the brains were electroporated with PB alone or a control pCAG-GFP construct expressing green fluorescence protein (GFP) at E14.5, the fluorescently labeled cells were primarily found within layers 2/3 and 4 of cortex on postnatal day 10 (P10) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The PB transposon system consisted a piggyBac transposon with the PB-tk-mRFP reporter and the Act-PBase helper plasmid of Act-PBase; these were provided by J-Y Lee 18 , 23 , 24 . The shRNA constructs, which are based on the pLKO_TRC001 vector, were obtained from the National RNAi Core Facility in Taiwan (Supplementary Table 4 ).…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, Sox2 has been discovered to be aberrantly expressed in cancer cells, including those of the lungs, brain, ovaries, bone, colon, skin, and breasts [ 8 ]-[ 15 ]. In many of these studies, Sox2 was found in the cancer stem cell population [ 7 ],[ 12 ],[ 16 ]-[ 22 ], supporting the hypothesis that cancer stemness is related to the aberrant expression of ESC proteins. It has been demonstrated that Sox2 promotes key tumorigenic properties in cancer cells, including enhanced proliferation, invasion, migration, colony formation, non-adherent stem cell-associated sphere formations in vitro , and tumorigenicity in vivo [ 8 ],[ 12 ],[ 19 ]-[ 24 ].…”
Section: Introductionmentioning
confidence: 87%
“…41 We modified this system by adding a firefly luciferase ( luc2 ) gene to the original dual-cistronic PB-2R construct to create a new PB-3R construct for two reasons. First, we wanted to overcome the low sensitivity of mRFP for optical imaging.…”
Section: Methodsmentioning
confidence: 99%